Effectiveness of allergic rhinitis treatments in real-life with a focus on MP-AzeFlu. Issue 5 (3rd May 2016) - Klimek, Ludger; Demoly, Pascal; Price, David
ABSTRACT: For any allergic rhinitis (AR) treatment, it is crucial to provide evidence not only of efficacy (assessed in randomized controlled trials (RCTs)) but also of effectiveness in real-life. Observational studies provide valuable data on the use and results associated with interventions prescribed in real-life. However, real-life evidence supporting available AR treatment options is sparse with effectiveness only established for oral antihistamines (desloratadine, ebastine), intranasal corticosteroids (mometasone furoate, fluticasone propionate (FP)), allergen immunotherapy and omalizumab. A novel intranasal formulation of azelastine hydrochloride and FP in a single spray (MP-AzeFlu) shows great promise, with the effectiveness observed in real-life exceeding that noted in RCTs. This review summarises real-life data on MP-AzeFlu, which provides rapid and sustained symptom control irrespective of patient age, AR phenotype or disease severity. We call for high quality real-life research in addition to RCTs to inform future AR treatment guidelines.